Hoe is de wereld eraan toe : 1991 - Brown, Lester R.; Flavin, Christopher; Postel, Sandra; Starke, Linda (Amsterdam : Milieudefensie, 1991)
Aanwinst van De Batselier, Norbert
Oorspronkelijke titel : "State of the World 1991"
Nederlands
Monografie